HUBUNGAN TINGKAT PENGETAHUAN IBU TERHADAP KELENGKAPAN PEMBERIAN IMUNISASI DASAR PADA BAYI 0-12 BULAN DI PUSKESMAS KUMUN - Soviarni Soviarni (Universitas Bengkulu, 2021)
In indonesia still found some problem of IMUNISAI which must overcome among him incomplete of him IMMUNIZE got by baby old age 12 months. Incomplete situation of him IMMUNIZE which is obtained age baby ! 2 months one of him because of lack of knowledge of mother about giving IMMUNIZE complete base of baby old age 12 months. This research aim to to know [relationmount knowledge of mother to equipment of giving IMMUNIZE base [at] baby 12 months in year kumun puskesmas 2018. analytic descriptive research desain with approach of sectional cross. Big of sampel 30 people with technique approach of sampling accidental result of research of menunjukan that there is relation him mount knowledge of mother to equipment of giving IMMUNIZE base at baby 12 months in kumun puskesmas with value of p-value = 0,003 ( p<0,05)